2008
DOI: 10.1111/j.1365-2044.2007.05097.x
|View full text |Cite
|
Sign up to set email alerts
|

Intubation of infants with Pierre Robin syndrome: the use of the paraglossal approach combined with a gum‐elastic bougie in six consecutive cases

Abstract: Summary Infants with Pierre Robin syndrome are known to be difficult to intubate. We evaluated the paraglossal approach combined with a gum elastic bougie for intubation of these infants. Whilst under general anaesthesia, a conventional laryngoscopy was performed; if it failed to obtain a laryngoscopic grade I or II view, intubation was attempted using a paraglossal approach and a gum elastic bougie. Six consecutive infants were studied. Conventional laryngoscopy failed in all infants whilst the paraglossal ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 13 publications
(13 reference statements)
1
37
0
Order By: Relevance
“…Similarly to Morfey [1] and Semjen's [2] experiences, we have found the straight laryngoscope blade more effective than curved blades for tracheal intubation of patients with micrognathia or short thyromental distances. In addition, we commonly use the straight blade for tracheal intubation of patients following radiotherapy for laryngeal and tongue base carcinoma where there is a low compliance of submandibular tissues.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Similarly to Morfey [1] and Semjen's [2] experiences, we have found the straight laryngoscope blade more effective than curved blades for tracheal intubation of patients with micrognathia or short thyromental distances. In addition, we commonly use the straight blade for tracheal intubation of patients following radiotherapy for laryngeal and tongue base carcinoma where there is a low compliance of submandibular tissues.…”
supporting
confidence: 74%
“…J. Edwards K. B. Greenland P. Allen P. Cumpston Royal Brisbane and Women's Hospital Qld, Australia E-mail: mikeed01@yahoo.com Both Yates et al and Biccard discuss the indications for peri-operative statin therapy and the current lack of evidence for starting statins in patients at risk of perioperative coronary events [1,2]. Whilst there is little evidence that statin therapy reduces peri-operative risk, we feel that it would be appropriate to initiate statin therapy in patients in whom it is medically indicated.…”
mentioning
confidence: 99%
“…A number of intubation techniques have been described in patients with PRS. These include awake intubation [13], use of the Airtrach Disposable Optical and Stortz DCI Video laryngoscopes [14,15], blind intubation using a lightwand [16], paraglossal approach with gum elastic bougie [17] and fibre-optic intubation, which in the authors' experience, is often easier via an LMA. Fortunately, these children become easier to manage as they grow up.…”
Section: Pierre Robin Sequencementioning
confidence: 99%
“…In other cases it is usually desirable to remove the LMA from the mouth. Techniques to accomplish this have been described in the literature (10)(11)(12)(13)(14). Osses et al (14) reported a similar technique to what we report, using an adult intubating stylette to push the ETT off the LMA, with several important differences.…”
Section: Discussionmentioning
confidence: 77%